The Pre-Raphaelites and their Keatsian Romanticism: An Analysis of the Renderings of 'The Eve of St Agnes and Isabella' - Díaz Morillo, Ester (Complutense Journal of English Studies, 2020)
This research examines the influence of Romantic poet John Keats on the Pre-Raphaelite Brotherhood, a Victorian artistic and literary movement. The aim of this paper is to prove how Keats became, moreover, a major connecting link between Romanticism and the Victorian era, thus enabling the continued existence of certain Romantic aesthetic features until the beginning of the twentieth century. In that sense, we will explore how this influence took shape and we will analyse Pre-Raphaelite works of art which have as source of inspiration some of Keats’s well-known poems (“Isabella; or, The Pot of Basil” and “The Eve of St. Agnes”). This examination will allow us to perceive the manner in which these artists devised their pictorial style based on Keatsian pictorialism in poetry, with a special emphasis on the significance of medievalism, and the beauty and sensuousness of his verses, and how they were transferred into their canvases.